Kepribadian Terbelah Dalam Perspektif Al-Quran - Nasution, M.Ag, Fauziah (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2019)
The definition of Fậsiq in the interpretation of al-Misbah is a person who has the nature and behavior out of obedience to God. This nature and behavior are ingrained to the culprit. At the lowest level of fậsiq is a person who commits a major sin, but in the highest tarap fậsiq is a person who disbelieves in Allah swt. The analysis of the fậsiq verses in the Qur'an according to the Qurash Shihab is addressed to: 1) The Jewish and Christian groups who do not believe in the Prophet Muhammadiyah, people who disobey leaders and underestimate minor sins. 2) People of the Prophets before the Prophet Muhammad. the lawless ones to the Prophets of Allah and the book of Allah. 3) Muslims who doubt Islam and commit major sins and get out of faith in Allah.Fậsiq is the impact of not developing fully the potential of jismiyah and ruhiyah man, which is characterized by incompatibility of functions with physical form and inability to use potential ‘aql, al-nafs and al-qalb. The balance of these two potentials will lead humans to become human beings, as reflected in the personality of the Prophet. Demensi rûh is very decisive in the formation of one's personality, although in his nature rh is sacred, but in reality it often slips and is tainted. In the empirical context, the process of forming, fostering and developing human personality is mainly to avoid the appearance of fậsiq personality, so religious counseling is needed with a fitrah approach, which begins with tazkiyah al-nafs, followed by tazkiyah al-‘aql and tazkiyah al-jism.Fậsiq dalam tafsir al-Misbah adalah orang yang memiliki sifat dan prilaku keluar dari ketaatan pada Allah. Sifat dan prilaku ini mendarah daging bagi pelakunya. Pada tarap terendah fậsiq  adalah orang yang melakukan dosa besar, namun pada tarap tertinggi fậsiq adalah orang yang kafir kepada Allah swt.  Analisis ayat-ayat fậsiq dalam Alquran menurut Qurash Shihab ditujukan kepada: 1) Golongan Yahudi dan Nasrani yang tidak mengimani Nabi Muhamamd saw., orang yang  membangkang pada pemimpin dan menyepelekan dosa kecil. 2) Umat Nabi-nabi sebelum Nabi Muhammad saw. yang durhaka kepada Nabi-Nabi Allah dan kitab Allah. 3) Kaum muslimin yang meragukan Islam dan melakukan dosa besar dan keluar dari keimanan kepada Allah. Fậsiq  merupakan dampak dari tidak  berkembangnya secara sempurna potensi jismiyah dan ruhiyah manusia,  yang ditandai dengan ketidaksesuaian fungsi dengan bentuk fisik dan ketidakmampuan menggunakan potensi ‘aql, al-nafs dan al-qalb. Keseimbangan  kedua potensi ini akan menghantarkan manusia menjadi insan kamil, seperti tercermin dalam kepribadian Rasulullah saw. Demensi rûh  sangat menentukan dalam pembentukan kepribadian seseorang, meski pada fitrahnya rûh adalah suci, namun dalam realita sering kali tergelincir dan ternodai. Dalam konteks empiris, maka proses pembentukan, pembinaan dan pengembangan kepribadian manusia terutama untuk menghindari munculnya kepribadian fậsiq, maka dibutuhkan konseling keagamaan dengan pendekatan fitrah, yang diawali diawali dengan tazkiyah al-nafs,dilanjutkan dengan tazkiyah al-‘aql dan tazkiyah al-jism.Key word: Fasiq – Kepribadian terbelah – Al-Quran-Tafsir Al-Misbah